Penggunaan Teknologi, Motivasi Kerja, Pelatihan, produktivitas kerja, Kepuasan Kerja Pada Bank Nagari Cabang Utama Padang - Ezi Rizki Aullia Putri; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of technology usage, work motivation, and job training on employee productivity through job satisfaction as an intervening variable at Bank Nagari Main Branch Padang. This research is motivated by the phenomenon of several job positions not achieving performance targets and the existence of work facility constraints, internet access limitations, and adaptation difficulties affecting employee satisfaction and productivity. This research uses a quantitative approach with a survey method. The population consists of all employees of Bank Nagari Main Branch Padang. The sampling technique used is a census/saturated sampling method, where all employees are taken as respondents. Data were collected through questionnaires and analyzed using path analysis with statistical software.The results indicate that technology usage and work motivation influence job satisfaction and employee productivity, while job training does not fully improve productivity directly. Job satisfaction acts as an intervening variable in the relationship between technology usage and work motivation on employee productivity. This shows that improving employee productivity is not only influenced by technical and training factors but also by the level of job satisfaction experienced by employees.The study concludes that employee productivity improvement can be achieved through optimizing technology usage and enhancing work motivation accompanied by increased job satisfaction